Endophytic Fungi as A Symbion in Polianthes tuberosa L.: Identification, Microscopic Observation, and Secondary Metabolite Analysis - Utami Sri Hastuti; Aulia Abdini; Dela Reni Puspitasari; Rodiah Amin Hamidah; Sylvana Bilqis Labibah (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Polianthes  tuberosa L. was known as an ornamental plants. People use this plant flower for ritual purpose because of the fragrant aroma. This plant rarely attacked by microorganism and usually stay healthy. Some endophytic fungi species live with P. tuberosaL. plant in mutualistic symbiosis interaction. This study was conducted to: (1) determine where the hyphae of endophytic fungi are located within the tissue of P. tuberosa L. plant petals and leaves, using findings from microscopic observations; (2) identify the species of endophytic fungi residing in the flower petals and leaves of P. tuberosa L.; and (3) ascertain the various secondary metabolites produced by each species of endophytic fungi. Methodology: P. tuberosa plant were obtained from flower market at Malang city. The leaves and flower petal parts were prepared for microscopic observation and identification. Cultures of each endophytic fungal species were grown on PDA plate medium, then cut into pieces measuring 5 x 1 cm and inoculated in PDB medium. These were shaken at a speed of 120 rpm for 7 days. After that, the liquid culture was centrifuged at 3000 rpm for 10 minutes. The contents of several secondary metabolites uses the supernatant of the liquid culture. The phytochemical analysis used spectrophotometry method.  Findings: The study findings are: (1) the endophytic fungi hyphae are located in stomata neighbor cells, the walls of xylem cells, epidermal cell walls, sponsa cell walls, and also within the petal epidermis cell walls of the flower; (2) eight endophytic fungi species have been identified; (3) every species of endophytic fungi generates flavonoids, alkaloids, tannins, saponins, and steroids, each with varying content levels. Contribution: Based on this research result, the endophytic fungi culture can be utilized as natural antibiotic source for better synthetic substitution. Besides that endophytic fungi also can be applied as antagonistic fungi to inhibite pathogenic fungi growth that attack some cultivated plant through appropriate research